2018
DOI: 10.1016/j.ijheh.2018.05.001
|View full text |Cite
|
Sign up to set email alerts
|

The association between urinary concentrations of phosphorous-containing flame retardant metabolites and semen parameters among men from a fertility clinic

Abstract: Detection rates were high for BDCIPP, DPHP, and ip-PPP. We did not observe consistent associations between PFR metabolites and semen parameters. Due to the high prevalence of exposure, further investigation of other potential health effects should be conducted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 40 publications
1
18
0
Order By: Relevance
“…Other PEFRs metabolites were more rarely analyzed. Tert-butyl phenyl phenyl phosphate (tb-PPP) and bis(2-ethylhexyl) phosphate (BEHP) were detected infrequently (Su et al, 2015;Butt et al, 2016;Castorina et al, 2017b;Hoffman et al, 2017a;Soubri et al, 2017;Carignan et al, 2018a and b;Deziel et al, 2018;He et al, 2018a;Hoffman et al, 2018;Ingle et al, 2018;Sun et al, 2018). Dibenzyl phosphate (DBzP) was not detected in urine samples collected in the U.S.A. (Romano et al, 2017;Jayatilaka et al, 2017;Ospina et al, 2018).…”
Section: General Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Other PEFRs metabolites were more rarely analyzed. Tert-butyl phenyl phenyl phosphate (tb-PPP) and bis(2-ethylhexyl) phosphate (BEHP) were detected infrequently (Su et al, 2015;Butt et al, 2016;Castorina et al, 2017b;Hoffman et al, 2017a;Soubri et al, 2017;Carignan et al, 2018a and b;Deziel et al, 2018;He et al, 2018a;Hoffman et al, 2018;Ingle et al, 2018;Sun et al, 2018). Dibenzyl phosphate (DBzP) was not detected in urine samples collected in the U.S.A. (Romano et al, 2017;Jayatilaka et al, 2017;Ospina et al, 2018).…”
Section: General Populationmentioning
confidence: 99%
“…This may be explained by differences in FR regulations, dietary habits, lifestyle, and use of PEFRs in household products and indoor environments (e.g., building material), between the various countries and/or study locations (Carignan et al, 2013;Butt et al, 2016;Lu et al, 2017;Chen et al, 2018;He et al, 2018b). Other factors were reported to have an impact on urinary PEFR metabolite concentrations, including timing (e.g., season of collection) (Hoffman et al, 2017a and b;Deziel et al, 2018;Ingle et al, 2018;Phillips et al, 2018), sex (e.g., women tend to have higher levels of DPHP than men, Hoffman et al, 2015b;Preston et al, 2017;He et al, 2018a;Ospina et al, 2018), behavior and activity patterns (e.g., hand washing and cleaning routines, nail painting) (Abdallah et al, 2016;Mendelsohn et al, 2016;He et al, 2018b) and age (Van den Lu et al, 2017;He et al, 2018a;Ospina et al, 2018;Sun et al, 2018). Urinary concentrations of the main PEFR metabolites were generally higher in toddlers than in adults (Butt et al, 2014 andCequier et al, 2015;Hoffman et al, 2015a;Van den Eede et al, 2015b;Chen et al, 2018;He et al, 2018a and b;Ospina et al, 2018).…”
Section: Possible Bias Limitations and Strengths Of The Reviewed Stumentioning
confidence: 99%
“…Our subset from the EARTH cohort consisted of 230 women and 229 men contributing one to five urine samples per participant ( n = 638 women and n = 335 men). Demographic characteristics of these women and men have been previously reported [25, 37]. Briefly, this sample consisted primarily of Caucasian (87%), nonsmoking (75%), and highly educated (57% hold graduate degree) women with an average age of 35 [25].…”
Section: Resultsmentioning
confidence: 99%
“…Distributions of PFRs have been previously reported for participants [25, 37]. Due to the low frequency of detectable concentrations, BCIPP was henceforth excluded in this analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Many studies have demonstrated the anti-androgenic effect on adults exposed to several chemical classes: e.g. pesticides [13], perfluorinated chemicals [39], brominated flame retardants [40], phthalates [41,42].…”
Section: Discussionmentioning
confidence: 99%